Economic policy: Protectionism as an elite strategy - Vo Phuong Mai Le; Patrick Minford; Eric Nowell (Cardiff University, Cardiff Business School, 2009)
The EU has pursued protectionist policies not merely in food but also in manufacturing at the customs union level. In services it has not dismantled much of the existing national protectionism. The economic costs are calculated here at some 3% of GDP for the UK and some 4% for the rest of the EU - or much larger under liberal planning assumptions. Added to its social interventionism, these costs suggest that the EU has put political integration before economic efficiency. This policymaking pattern suggests that European elites believe their position would be threatened by the domestic effects of world competition.
Keywords: F13; F14; 330; protectionism; manufactures; anti-dumping; tariff equivalent; customs union; competition; Protektionismus; Verarbeitendes Gewerbe; Zollpolitik; Wettbewerb; Wohlfahrtsanalyse; Politisches Ziel; Europäische Integration; EU-Staaten